Improvement in glycated haemoglobin evaluated by baseline body mass index: a meta‐analysis of the liraglutide phase III clinical trial programme. Issue 7 (2nd February 2016) - Montanya, E.; Fonseca, V.; Colagiuri, S.; Blonde, L.; Donsmark, M.; Nauck, M. A.
Abstract : In the liraglutide clinical trial programme, liraglutide 1.2 and 1.8 mg were found to effectively lower glycated haemoglobin (HbA1c) in patients with type 2 diabetes (T2D). It is unknown whether baseline body mass index (BMI) is a predictor of change in HbA1c observed during a clinical trial with liraglutide or placebo treatment. The present meta‐analysis of patient‐level data, using pooled data from seven phase III trials [LEAD‐1–6 and the liraglutide versus sitagliptin trial (LIRA–DPP‐4)] for liraglutide 1.2, 1.8 mg and placebo (n = 3222), identified no significant correlation between baseline BMI (<20 kg/m 2 up to 45 kg/m 2 ) and HbA1c reduction for placebo or liraglutide 1.2 mg, and a modest, clinically non‐relevant, association for liraglutide 1.8 mg [−0.010 (95% confidence interval −0.020, −0.001)], whereby a 10 kg/m 2 increase in baseline BMI corresponded to 0.10%‐point (1.1 mmol/mol) greater HbA1c reduction. In summary, reductions in HbA1c obtained during clinical trials with liraglutide or placebo treatment were independent of baseline BMI.